Sustainability factors for entrepreneurship phases in emerging economies: Nigeria and South Africa - Akinyemi, Folashade Oyeyemi (My University, 2016)
Many research findings have highlighted the importance of numerous sustainability factors needed for the growth and development of entrepreneurship. Sustainability factors such as finance, environmental stability, and good management practices determine the likely success of entrepreneurial activities. These factors are sometimes referred to as success factors and have been found to boost entrepreneurial activities as well as enhance the industrialisation process in many economies. Interestingly, entrepreneurship evolves across distinctive phases from conception to becoming a full-fledged enterprise, with sustainability factors determining the extent of success in each identifiable phase. This study was, therefore, designed to ascertain the most crucial sustainability factors necessary for navigating through entrepreneurship phases in two major emerging economies in Africa- Nigeria and South Africa. It was also designed to estimate the probability of successfully moving from one entrepreneurship phase to another, with a comparative analysis of the findings from these distinctly representative economies. Primary data was collected through administration of questionnaire to and in-depth interviews of selected respondents in the commercial capital cities of the two sample economies- Lagos and Johannesburg. STATA and Atlas Ti were used for the quantitative and qualitative analysis, respectively. The quantitative analysis was in two stages; stage one involved descriptive statistics while stage two involved inferential statistics. The results showed that relevant sustainability factors vary across entrepreneurship phases, and were peculiar to either economy. Further, some similarities exist in the sustainability factors relevant in identical phases in both economies. The results also confirmed that some factors are more crucial than others in some entrepreneurship phases. Furthermore, the probability estimates of moving from one entrepreneurship phase to another in both economies revealed the most volatile and least volatile phases in the entrepreneurship evolution. Based on the findings of this study, some policy suggestions are made, and areas for further research are identified. Financial and non-financial supports are also recommended for entrepreneurs in the volatile phases. Given the relative importance of the sustainability xii factors in each entrepreneurship phase and economy, the policy makers and other stakeholders would be aware of the core areas to channel necessary interventions. Many research findings have highlighted the importance of numerous sustainability factors needed for the growth and development of entrepreneurship. Sustainability factors such as finance, environmental stability, and good management practices determine the likely success of entrepreneurial activities. These factors are sometimes referred to as success factors and have been found to boost entrepreneurial activities as well as enhance the industrialisation process in many economies. Interestingly, entrepreneurship evolves across distinctive phases from conception to becoming a full-fledged enterprise, with sustainability factors determining the extent of success in each identifiable phase. This study was, therefore, designed to ascertain the most crucial sustainability factors necessary for navigating through entrepreneurship phases in two major emerging economies in Africa- Nigeria and South Africa. It was also designed to estimate the probability of successfully moving from one entrepreneurship phase to another, with a comparative analysis of the findings from these distinctly representative economies. Primary data was collected through administration of questionnaire to and in-depth interviews of selected respondents in the commercial capital cities of the two sample economies- Lagos and Johannesburg. STATA and Atlas Ti were used for the quantitative and qualitative analysis, respectively. The quantitative analysis was in two stages; stage one involved descriptive statistics while stage two involved inferential statistics. The results showed that relevant sustainability factors vary across entrepreneurship phases, and were peculiar to either economy. Further, some similarities exist in the sustainability factors relevant in identical phases in both economies. The results also confirmed that some factors are more crucial than others in some entrepreneurship phases. Furthermore, the probability estimates of moving from one entrepreneurship phase to another in both economies revealed the most volatile and least volatile phases in the entrepreneurship evolution. Based on the findings of this study, some policy suggestions are made, and areas for further research are identified. Financial and non-financial supports are also recommended for entrepreneurs in the volatile phases. Given the relative importance of the sustainability xii factors in each entrepreneurship phase and economy, the policy makers and other stakeholders would be aware of the core areas to channel necessary interventions. Many research findings have highlighted the importance of numerous sustainability factors needed for the growth and development of entrepreneurship. Sustainability factors such as finance, environmental stability, and good management practices determine the likely success of entrepreneurial activities. These factors are sometimes referred to as success factors and have been found to boost entrepreneurial activities as well as enhance the industrialisation process in many economies. Interestingly, entrepreneurship evolves across distinctive phases from conception to becoming a full-fledged enterprise, with sustainability factors determining the extent of success in each identifiable phase. This study was, therefore, designed to ascertain the most crucial sustainability factors necessary for navigating through entrepreneurship phases in two major emerging economies in Africa- Nigeria and South Africa. It was also designed to estimate the probability of successfully moving from one entrepreneurship phase to another, with a comparative analysis of the findings from these distinctly representative economies. Primary data was collected through administration of questionnaire to and in-depth interviews of selected respondents in the commercial capital cities of the two sample economies- Lagos and Johannesburg. STATA and Atlas Ti were used for the quantitative and qualitative analysis, respectively. The quantitative analysis was in two stages; stage one involved descriptive statistics while stage two involved inferential statistics. The results showed that relevant sustainability factors vary across entrepreneurship phases, and were peculiar to either economy. Further, some similarities exist in the sustainability factors relevant in identical phases in both economies. The results also confirmed that some factors are more crucial than others in some entrepreneurship phases. Furthermore, the probability estimates of moving from one entrepreneurship phase to another in both economies revealed the most volatile and least volatile phases in the entrepreneurship evolution. Based on the findings of this study, some policy suggestions are made, and areas for further research are identified. Financial and non-financial supports are also recommended for entrepreneurs in the volatile phases. Given the relative importance of the sustainability xii factors in each entrepreneurship phase and economy, the policy makers and other stakeholders would be aware of the core areas to channel necessary interventions.
Thesis submitted to the Wits Business School, Faculty of Commerce, Law, and Management, in fulfilment of the requirements for the Doctorate Degree in Entrepreneurship University of the Witwatersrand September 2016
Keywords: Entrepreneurship--Nigeria; Entrepreneurship--South Africa; Sustainable development--Nigeria; Sustainable development--South Africa; Nigeria--Economic development; South Africa--Economic development